Comparative Genomic Analysis of Two Xanthomonas oryzae pv. oryzae Strains Isolated From Low Land and High Mountain Paddies in Guangxi, China - Li, Tianjiao; Li, Yiming; Ma, Xiuguo; Dan, Xue; Huang, Xianjiao; Li, Qinying; Lei, Shimin; Zhang, Zhengchun; Huang, Sheng; Jiang, Wei; Yu, Yanhua; He, Yong-Qiang (Frontiers in Microbiology, 2022)
Xanthomonas oryzae pv. textitoryzae (Xoo) is a causal agent of rice bacterial leaf blight (BLB), the major rice disease, which is seriously constraining rice production in Asia. The interaction between Xoo and rice is in a dynamic process, essentially the co-evolution. Tracking the occurrence of plant diseases and identifying the epidemic pathogens in time are critical to assessing the epidemic disease status and understanding the pathogen evolution. In 2020, the occurrences of rice BLB were spotted in many places of Guangxi, the major rice growing region in China. Two of the 2020-epidemic Xoo strains, namely, GXO20-01 and GXO20-06, were isolated from low land and high mountain paddies in Guangxi, respectively, and were demonstrated to be race R8 of Chinese Xoo strains, but with significantly different virulence on certain susceptible varieties of rice. The HiFi PacBio sequencing revealed that GXO20-01 and GXO20-06 share the highly syntenic genome structures and the major genome contents, but only differ in <10 genes, including one gene encoding for transcription activator-like effector (TALE). A phylogenomic analysis grouped GXO20-01 and GXO20-06 into the PX-A lineage, stood close to PXO563 and PXO71 strains, but stood away from the other Chinese Xoo strains; for example, the JL25 and YC11. A comparative genomic analysis revealed that the major pathogenicity/virulence genes are conserved in two, newly isolated Xoo strains and the other Xoo strains in PX-A lineage, including the majority genes for the TALomes. The genomic differences between the Xoo strains were pinpointed to a few tal genes, which were variable in both their numbers and sequences, even between GXO20-01 and GXO20-06, the two 2020-epidemic Xoo strains. The study further revealed the instability and variability of tal genes in Xoo and highlighted the utility of HiFi long-read sequencing in TALE analysis and pathogen tracking.